Development of a high frequency triple output SMPS for audio/video power supply & HP charging - Soh, Lin Heng (2015)
High frequency triple outputs Switch Mode Power Supply (SMPS) was analysed and designed by both software simulation and hardware implementation approach. Three output voltages were designed as 3.3V, 5V, and 12V, each of its rated current is 0.1A, 3A, and 0.8A respectively. Different topologies of SMPS have been analysed and Flyback topology was chosen in this design application. PSIM software was used to analyse the triple output voltages with respect to input voltage fluctuation. Functional C block was applied to simulate feedback controller, Pulse Width Modulation (PWM) controller, and voltage regulator. Design calculation of each component was carried out, with consideration of Electromagnetic Interference (EMI), power factor correction, surge protection, output passive filters, switching transformer specification, switching frequency & duty cycle, and input voltage range. OrCAD software was used to design the schematic and layout of the Printed Circuit Board (PCB). Hardware implementation was based on the computed design values, performance results were tested and satisfied with the design requirements. VIPer53E switching IC was used, the switching frequency was set at 40 kHz and feedback sensing was taken from the 5V output. The completed SMPS achieved high efficiency (≈70%) with low implementation cost (≈$50). Output voltages remained stable throughout the universal input range (90Vac~260Vac).